Kekuasaan: Determinan Sosial dan Kebudayaan Penyakit Tuberkulosis Paru di Cinangka Serang Banten - M Farid (Universitas Andalas, 2022)
The backgrounds of this research are the reality of pulmonary tuberculosis cases in Indonesia which has never been resolved since the colonial era until now, and the ignorance of biomedical experts to the results of medical anthropology research on pulmonary tuberculosis. Therefore, this study tries to get out of the usual themes of medical anthropological research and offer “power” as a new theme in medical anthropological research on pulmonary tuberculosis. The method used is a qualitative method with an ethnographic approach to describe the process of occurrence and transmission of pulmonary tuberculosis. The findings of this research are; (1) the knowledge of society in Cinangka Serang Banten regarding pulmonary tuberculosis is constructed by staff of public health center (puskesmas), as well as personalistic and naturalistic traditional healers, (2) social process, as a form of power implementation, can stimulate, encourage, or even facilitate the biological process of pulmonary tuberculosis, (3) the use of power issue in medical anthropology perspective for the understanding disease is significant as one of the themes in pulmonary tuberculosis research. The effect of these findings is; to stimulate the dynamization of theory and method in medical anthropology; reconstruct the way of thinking in the study of disease; provide a conceptual contribution to overcoming pulmonary tuberculosis.